Pemberdayaan Masyarakat melalui Pemanfaatan Eco-Enzyme dalam Pengolahan Air Limbah dan Perawatan Drainase di Desa Iker-Iker Geger Cerme Gresik (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Domestic wastewater and inadequate drainage maintenance increase environmental and public-health risks, while household organic residues remain underused. This community service program strengthened residents’ literacy for cautious eco-enzyme use as a supplementary option in wastewater management and drainage maintenance in Iker-Iker Geger Village, Cerme, Gresik. A participatory action-learning approach included situation mapping, local coordination, sanitation education, material demonstration, guided discussion, and reflective evaluation. Baseline data were obtained from the 2025 Gresik Regency Domestic Wastewater Management Master Plan; program outputs were assessed through observation, documentation, discussion records, and demonstration materials. The activities produced an education forum, product examples, clarification of the 1:3:10 fermentation composition, and a follow-up framework combining source control, physical drain cleaning, cautious pilot application, and water-quality monitoring. Eco-enzyme was positioned as a supplement, not a replacement for standard wastewater treatment, septic-system management, or sediment and solid-waste removal. Because no pretest-posttest survey or laboratory testing of BOD, COD, TSS, dissolved oxygen, and pH was conducted, outcomes are limited to implementation, educational outputs, and community readiness. A monitored pilot with standardized dosage and before-after testing is recommended.